Is wealth becoming more polarized in the United States? - Conchita D'Ambrosio; Edward N. Wolff (Levy Economics Institute of Bard College, 2001)
Recent work has documented a rising degree of wealth inequality in the United States between 1983 and 1998. In this paper, we look at another dimension of the distribution, polarization. Using techniques developed by Esteban and Ray (1994) and further extended by D'Ambrosio (2001), we examine whether a similar pattern exists with regard to trends in wealth polarization over this period. The approach here followed provides a decomposition method, based on counterfactual distributions, which allows one to monitor what factors modified the entire distribution and where precisely on the distribution these factors had an effect. An index of polarization is provided as well as summary statistics of the observed movements and of distance and divergence among the estimated and the counterfactual distributions. The decomposition method is applied to US data on the distribution of wealth between 1983 and 1998. We find that polarization between homeowners and tenants, as well as among different educational groups, continuously increased from 1983 to 1998, while polarization by income classes groups continuously decreased. In contrast, polarization by racial group first increased from 1983 to 1989 and then declined from 1989 to 1998, while polarization by age groups followed the opposite pattern. We also find that most of the observed variation in the overall wealth density over the 1983-98 period can be attributed to changes of the within-group wealth densities rather than to changes in household characteristics over the period.
Keywords: 330